2011
DOI: 10.4172/2155-9899.s1-011
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Factors and Cytokines in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is a sight-threatening complication of both type-1 and type-2 diabetes. The recent success of treatments inhibiting the function of vascular endothelial growth factor (VEGF) demonstrates that specific targeting of a growth factor responsible for vascular permeability and growth is an effective means of treating DRtargets involved in the control of retinal vascular function. However, additional treatment options and preventative measures are still needed and these require a greater und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 100 publications
(122 reference statements)
3
86
0
1
Order By: Relevance
“…Activated microglia produce proinflammatory cytokines (e.g. VEGF and TNF-α) in early DR, promoting damage to the retinal neurons and vasculature [31]. To assess microglial activation, retinal flat mounts from db/db mice were co-labelled with isolectin B4 and Iba-1 [32] (ESM Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Activated microglia produce proinflammatory cytokines (e.g. VEGF and TNF-α) in early DR, promoting damage to the retinal neurons and vasculature [31]. To assess microglial activation, retinal flat mounts from db/db mice were co-labelled with isolectin B4 and Iba-1 [32] (ESM Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The key pharmacologic biomarker of CCR2 receptor antagonism, increases in MCP-1, was measured from peripheral blood samples, rather than sampling from vitreous fluid (vitrectomy), which in this study would have exposed the patient to risk. 41 However, the substantial rise in MCP-1 levels observed throughout the dosing period were similar to the maximum observed in healthy volunteers, which did not increase with higher doses of PF-04634817 (Pfizer data on file [NCT01098877 and NCT01140672]). Recent evaluation of another CCR2 inhibitor, CCX140-B, by de Zeeuw et al 43 in patients with type 2 diabetes and nephropathy also showed increases in serum MCP-1, but only at the highest dose studied.…”
Section: Discussionmentioning
confidence: 99%
“…As the relative contributions of multiple angiogenic and inflammatory factors associated with diabetic retinopathy/DME remain to be fully elucidated, 41 it is possible that CCR2/5 antagonism by PF-04634817 does not result in inhibition of a key pathway, or that the pathophysiologic function of these specific populations of receptors can be taken on by other mechanisms once CCR2/5 receptors are blocked.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Several studies have indicated that there is a significant increase in the levels of proangiogenic and proinflammatory factors and cytokines (e.g., vascular endothelial growth factor, IL-8, TNF-a, IL-6, and IL-1b) in the vitreous of a patient with diabetic retinopathy. [40][41][42][43] These findings have led to the emergence of several novel treatment modalities based on the administration of antivascular endothelial growth factor agents and corticosteroids to the diseased retina. 44,45 Corticosteroids are an attractive option due to their broad range of actions including anti-inflammatory and antiangiogenic effects.…”
Section: Discussionmentioning
confidence: 99%